The unfolded protein response and proteostasis in Alzheimer disease: Preferential activation of autophagy by endoplasmic reticulum stress - Scheper, Wiep (Landes Bioscience, 2011)
Protein folding stress in the endoplasmic reticulum (ER) may lead to activation of the unfolded protein response (UPR), aimed to restore proteostasis in the ER. Previously, we demonstrated that UPR activation is an early event in Alzheimer disease (AD) brain. In our recent work we investigated whether activation of the UPR is employed to enhance the capacity of the ubiquitin proteasome system or autophagy in neuronal cells. We showed that the levels, composition and activity of the proteasome are not regulated by the UPR. In contrast, UPR activation enhances autophagy and LC3 levels are increased in neurons displaying UPR activation in AD brain. Our data suggest that autophagy is the major degradational pathway following UPR activation in neuronal cells and indicate a connection between UPR activation and autophagic pathology in AD brain.